2021
DOI: 10.1111/exd.14288
|View full text |Cite
|
Sign up to set email alerts
|

A phytic acid analogue INS‐3001 prevents ectopic calcification in an Abcc6−/− mouse model of pseudoxanthoma elasticum

Abstract: Pseudoxanthoma elasticum (PXE), a prototype of heritable ectopic calcification disorders, affects the skin, eyes and the cardiovascular system due to inactivating mutations in the ABCC6 gene. There is no effective treatment for the systemic manifestations of PXE. In this study, the efficacy of INS‐3001, an analogue of phytic acid, was tested for inhibition of ectopic calcification in an Abcc6−/− mouse model of PXE. In prevention study, Abcc6−/− mice, at 6 weeks of age, the time of onset of ectopic calcificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…IP6 has poor bioavailability and pharmacokinetics, which has prompted the development of a series of derivatives [ 211 ]. These were tested in Abcc6 −/− mice [ 149 ]. Compound INS-3001 was found to be superior in calcification inhibition both in vitro and in vivo and displayed a better plasma half-life as compared with IP6 [ 211 ].…”
Section: Rescue and Therapeutic Solutionsmentioning
confidence: 99%
“…IP6 has poor bioavailability and pharmacokinetics, which has prompted the development of a series of derivatives [ 211 ]. These were tested in Abcc6 −/− mice [ 149 ]. Compound INS-3001 was found to be superior in calcification inhibition both in vitro and in vivo and displayed a better plasma half-life as compared with IP6 [ 211 ].…”
Section: Rescue and Therapeutic Solutionsmentioning
confidence: 99%
“…When it occurs in joints, heart valves, and blood vessels, it may lead to very serious clinical consequences. Current research on ectopic calcification focuses on the development of effective mineralization inhibitors and mechanisms for inhibiting mineralization in vivo; e.g., Jacobs et al 85 found that INS-3001 (a phytic acid analogue) stabilized calcification that had already appeared at the start of treatment in the Abcc6/mouse PXE model; Barinda et al 86 found that macrophages highly expressed the enzyme carbonic anhydrase 2 (CA2), which played a key role in decalcification of ectopic calcification. In addition, metabolic bone diseases such as chondromalacia and bone Paget's disease are mostly treated with biologic factors in combination with other physical therapy methods.…”
Section: Osteoporosis Repairmentioning
confidence: 99%
“…Therefore, Schantl et al generated the inositol phosphate analog (OEG2)2-IP4, with more favorable pharmacokinetics and an extended half -life, which is distributed in the US as INS-3001 [ 214 ]. INS-3001 was administered subcutaneously to ABCC6 −/− mice, either continuously via subcutaneous implanted osmotic pumps, or via thrice or once weekly subcutaneous injection [ 216 ]. At a dosage of 4 mg/kg/day of INS-3001, by either continuous or cyclical administration, ectopic calcification was prevented or preserved.…”
Section: Therapeutic Approachesmentioning
confidence: 99%